Rearrangements involving repeated sequences within a P element preferentially occur between units close to the transposon extremities. - Paques, F.; Bucheton, B.; Wegnez, M. (Genetics, 1996)
In a previous report we described rearrangements occurring at a high rate (30% of the progeny of dysgenic flies) within a cluster of 5S genes internal to a P element. These events were characterized as precise amplifications and deletions of 5S units. Here we analyze recombination events within P elements containing two repeated arrays of 5S genes flanking a central white gene. Deletions (50%) and duplications (3%) of the white gene together with various amounts of flanking 5S genes were observed. These recombinations occur preferentially between the most external 5S units of P transposons. Such rearrangements could be favored by interactions between the proteins bound to the P terminal sequences.